Factors Influencing Health and Self-Care of the Elderly In Madina Municipality, Greater Accra Region, Ghana - Opio, J.P. (University of Ghana, 2018)
Background: The growth of the aging population is known to lead to an upsurge in problems for the older people and to the society. A considerable proportion of older adults are experiencing added challenges in maintaining their health. With the eroded traditional family support systems and no formal institutions to take care of the elderly, it is not known what self-care interventions if any exist in the community and if so what factors influence their presence or absence. Self-care interventions have been highlighted as the main means contributing to a better health of older adults. The study investigated the association between lifestyle, socio-demographic determinants on perceived health and self-care, describe the health and self-care interventions and finally perceived Health state characteristics of the elderly. Methodology: The study used a descriptive cross-sectional design. A total sample size of 375 elderly persons (60 year and above), living in Madina sub-district of La-Nkwantanag Municipal assembly completed a WHO-SAGE (Study of Global Aging) adapted structured questionnaire designed for this study. Descriptive statistics was used for analyzing the data and binary logistic regression was used to determine the relationship between lifestyle, socio-demographic, self-care on Health status. Results: The results showed no significant relationship between sex of the respondent and Self-reported Health status, however significant relationship were noted between Age and poor health status with more advanced elderly less likely able to report selves with Good health status. Married elderly persons were among those reported with Good health status. Elderly from traditional extended families were more by about twice likely to report having good health status. Older persons highly participating in religious activities were generally reported in good self-reported health status and those living a responsible self-care were about 46 times more likely to report selves as with a good health status than those with abandoned self-care. Chronic Illness was prevalent among elderly at 72.5%. Conclusion: The present study has contributed significantly to the current literature on Elderly population, particularly as concerns predictors of Health and Self-care. It provides the best possible evidence on elderly research. Hopefully early health promotional interventions targeting the elderly should be prioritized at all levels.
Thesis (MPh)
Keywords: Population; Self-Care; Elderly; Madina; Interventions; Prioritized